Implementation and Feasibility Study of Solar-powered Streetlighting Systems in Rural Community Area - Pratama Sakca Garda; Namyra Alissa Raden Ajeng Dhea; Nafis Raihan Fauzan; Arrayyan Ahmad Zaki; Putra Karisma Trinanda (E3S Web of Conferences, 2023)
Green technology plays a pivotal role in establishing a sustainable and secure environment for citizens by introducing smart solarpowered streetlights. Numerous cities have embraced this eco-friendly approach by incorporating solar-powered street lighting systems (SP-SLS) into their infrastructure. Despite its popularity, rural communities, especially in Indonesia, have yet to fully experience the advantages of this green technology. Nonetheless, the effectiveness of SP-SLS installation in relation to geographic conditions and shadowing levels remains unidentified. Addressing this knowledge gap, our study proposes a comprehensive design and feasibility analysis of solar-powered street lighting systems tailored for rural Indonesian communities, with the primary aim of curtailing power consumption and minimizing environmental impact. Our proposed green technology entails the deployment of ten streetlamps, each equipped with an integrated solar generator and an adaptive night-time lighting system employing standard LEDs. Furthermore, our design accounts for varying shadow levels during installation to ensure optimal lighting outcomes. The results of this implementation showcase a remarkable decrease in electricity usage attributed to the adoption of green technology. Additionally, the application of this lighting system demonstrates a reduction in the emission of 4417 kg/year of greenhouse gases into the atmosphere.